A thermal control coating and its application
By using sheet-shaped wide bandgap filler and granular wide bandgap filler of the clad layer in thermally controlled coatings, combined with the filler ratio that defines the particle size and shape, the problem of low reflectivity of existing thermally controlled coatings under low color base ratio and thin coating conditions is solved, and efficient solar light reflection and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202411463281.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-21
AI Technical Summary
It is difficult for existing thermally controlled coatings to achieve a solar reflectivity of more than 90% under low color base ratio and thin coating conditions, and the construction difficulty and cost are high.
The thermally controlled coating is used to coat the high-refractive index coating on the surface of the sheet-shaped wide band-gap filler. Combining the sheet-shaped and granular wide band-gap filler, the particle size of the granular filler and the thickness and diameter of the sheet-shaped filler are defined to ensure high reflectivity under low color-based ratio and thin coating conditions.
With a coating thickness of 70μm, the solar reflectivity of more than 90% is achieved, which simplifies the type of coating and the construction process and improves mechanical and weather resistance.
Smart Images

Figure CN118956218B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to a thermal control coating and application thereof. Background Art
[0002] Commercial thermal control coatings usually use titanium dioxide, calcium carbonate, barium sulfate, aluminum oxide, and silicon dioxide to reflect sunlight, reduce the heat gain of the coating surface, and then radiate part of the heat to the outside through high broad-spectrum emissivity to achieve the purpose of reducing and controlling the surface temperature of the object. Titanium dioxide has a high refractive index and is the most widely used reflective material, but due to its narrow bandgap (such as Figure 1 As shown in the figure, it strongly absorbs the ultraviolet rays (200~380nm part) in sunlight, resulting in a reflectivity of less than 90% for the coating with titanium dioxide as the main medium; while the refractive index of wide bandgap media such as calcium carbonate, barium sulfate, aluminum oxide, and silicon dioxide is low, and the scattering efficiency of light is low. To achieve a solar reflectivity of more than 90%, there are usually two ways. First, a large proportion of reflective medium is added. For example, calcium carbonate and barium sulfate coatings require a pigment-to-base ratio (mass ratio of filler to resin dry weight) of more than 8 to achieve good optical properties. A large amount of filler added will cause the resin to not completely wrap the filler surface, which will cause coating hole defects and mechanical and weather resistance problems; second, increase the coating thickness so that the incident light can encounter more reflective media and increase the probability of light scattering. Calcium carbonate and barium sulfate coatings often require a coating thickness of more than 0.5mm to achieve a solar reflectivity of more than 90%, which increases the difficulty and cost of construction and application. Some commercial coatings use a double-layer structure to improve reflectivity. The first layer uses titanium dioxide to highly reflect visible light and near-infrared in the sun, and the second layer uses wide bandgap materials to reflect ultraviolet rays, thereby achieving an overall solar reflectivity of more than 90%. This method also brings about the problem of complicated coating types and construction. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a thermal control coating and its application. The thermal control coating provided by the present invention has a high solar reflectivity of >90% under the conditions of low pigment-to-base ratio and thin coating.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a thermal control coating, comprising the following components in percentage by mass:
[0006] Resin 15~30%, dispersant 0.5~3%, defoamer 0.5~3%, oriented alignment agent 0.5~3%, lamellar wide bandgap filler 10~40%, granular wide bandgap filler 10~40% and the rest solvent;
[0007] The particle size of the granular wide bandgap filler is 5nm~10μm;
[0008] The flaky wide bandgap filler comprises a flaky wide bandgap material and a coating layer wrapping the flaky wide bandgap material, wherein the coating layer is made of TiO2, SiO2 or Al2O3;
[0009] The sheet-like wide bandgap material has a thickness of 5-500 nm, a diameter of 3-50 μm, and a diameter / thickness ratio of 10-100.
[0010] Preferably, the coating layer has a thickness of 100-300 nm.
[0011] Preferably, the diameter of the sheet-shaped wide bandgap material is 5-10 μm.
[0012] Preferably, the diameter / thickness of the sheet-like wide bandgap material is 15-30.
[0013] Preferably, the particle size of the granular wide bandgap filler is 6-500 nm.
[0014] Preferably, the particle size of the granular wide bandgap filler is 10-20 nm.
[0015] Preferably, the types of the flaky wide bandgap material and the granular wide bandgap filler independently include one or more of calcium carbonate, barium sulfate, aluminum oxide, silicon dioxide, magnesium oxide and boron nitride.
[0016] Preferably, the resin includes one or more of acrylic resin, epoxy resin, polyester resin, polyurethane resin and fluorocarbon resin.
[0017] Preferably, the alignment aid comprises cellulose and / or modified polyamide wax.
[0018] The present invention also provides the application of the thermal control coating described in the above technical solution in the fields of construction, petrochemical industry, logistics and transportation, food storage, power communication and spacecraft.
[0019] The invention provides a thermal control coating, comprising the following components in mass percentage: 15-30% of resin, 0.5-3% of dispersant, 0.5-3% of defoamer, 0.5-3% of directional arrangement auxiliary agent, 10-40% of lamellar wide bandgap filler, 10-40% of granular wide bandgap filler and the remainder of solvent; the particle size of the granular wide bandgap filler is 5nm-10μm; the thickness of the lamellar wide bandgap filler is 5-500nm, the diameter is 3-50μm, and the diameter / thickness is 10-100; the lamellar wide bandgap filler comprises a lamellar wide bandgap material and a coating layer wrapping the lamellar wide bandgap material, and the coating layer is made of TiO2, SiO2 or Al2O3.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention coats a high refractive index coating layer on the surface of a flaky wide bandgap material, uses a flaky wide bandgap filler and a granular wide bandgap filler as a reflective medium, and combines the particle size of the granular wide bandgap filler, the thickness, diameter and diameter / thickness of the flaky wide bandgap material to limit the particle size, and the thickness, diameter and diameter / thickness of the flaky wide bandgap material. Under the conditions of a low pigment-to-base ratio (≤2.5) and a thin coating (below 100 μm), a thermal control coating with high solar reflectivity (>90%) can be prepared. The thermal control coating prepared by the present invention obtains a solar reflectivity of more than 90% at 70 μm, has a single type of coating, and is simple to construct. Since the pigment-to-base ratio is low and the coating is defect-free, it has good mechanical and weather resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the principle of solar reflectivity of different coatings;
[0023] Figure 2 This is the SEM image of flaky alumina coated with titanium dioxide;
[0024] Figure 3 The solar reflectance curves of the thermal control coating of Example 1 and the coating of Comparative Example 1;
[0025] Figure 4 The reflectivity curves of the coatings of Example 1 and Comparative 2 are shown. DETAILED DESCRIPTION
[0026] The present invention provides a thermal control coating, comprising the following components in percentage by mass:
[0027] Resin 15~30%, dispersant 0.5~3%, defoamer 0.5~3%, oriented alignment agent 0.5~3%, lamellar wide bandgap filler 20~40%, granular wide bandgap filler 10~20% and the rest solvent;
[0028] The particle size of the granular wide bandgap filler is 5nm~10μm;
[0029] The flaky wide bandgap filler comprises a flaky wide bandgap material and a coating layer wrapping the flaky wide bandgap material, wherein the coating layer is made of TiO2, SiO2 or Al2O3;
[0030] The sheet-shaped wide bandgap material has a thickness of 5-500 nm, a diameter of 3-50 μm, and a diameter / thickness ratio of 10-100.
[0031] Taking TiO2-wrapped Al2O3 (lamellar Al2O3@TiO2) as an example, Figure 1Figure 3 is a schematic diagram of the principle of solar reflectivity of different coatings, where a is the only alumina filler. Due to its low refractive index, the scattering efficiency of light is low, and a large pigment-to-base ratio needs to be added to obtain a high emissivity, which will cause coating defects; b is the oriented surface-coated titanium dioxide lamellar alumina that has a mirror reflection effect on light, and the enhanced birefringence effect and mirror reflection improve the reflection efficiency of light; c is the random arrangement of the lamellar materials on the surface, which weakens the mirror reflection to a certain extent, resulting in a decrease in the reflectivity of the visible light; d is the orderly arrangement of the lamellar materials on the surface, and the granular alumina further scatters light on the basis of b, thereby improving the overall solar reflectivity of the coating.
[0032] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.
[0033] The mass percentage of the flaky wide bandgap filler in the thermal control coating provided by the present invention is preferably 13-33%, specifically 10%, 13%, 33% or 40%.
[0034] In the present invention, the flaky wide bandgap filler comprises a flaky wide bandgap material and a coating layer wrapping the flaky wide bandgap material, the coating layer is made of TiO2, SiO2 or Al2O3, and the coating layer has a high refractive index.
[0035] In the present invention, the thickness of the coating layer is preferably 100-300 nm, specifically 100, 200 or 300 nm.
[0036] In the present invention, the diameter of the sheet-like wide bandgap material is preferably 5-10 μm, specifically 5, 10 or 50 μm.
[0037] In the present invention, the diameter / thickness of the sheet-like wide bandgap material is preferably 15-30, specifically 10, 15, 30 or 100.
[0038] In the present invention, the type of the sheet-like wide bandgap material preferably includes one or more of calcium carbonate, barium sulfate, aluminum oxide, silicon dioxide, magnesium oxide and boron nitride.
[0039] The present invention has no particular limitation on the specific preparation method of the flaky wide bandgap filler, and it can be prepared by methods well known to those skilled in the art, such as wet coating, vapor deposition or solid coating.
[0040] The preparation method of the flaky wide bandgap filler is described below by taking wet coating as an example.
[0041] The flaky wide bandgap material is dispersed in water to obtain a suspension having a concentration of 5wt%. The suspension is heated to 80°C, and then a 2mol / L TiCl4 solution is added dropwise to the suspension. The pH value is adjusted to 6 using a NaOH solution, and the stirring speed is controlled to 500rpm. The reacted solution is centrifuged after standing for 2h, and the solid is washed with deionized water. The centrifugal washing steps are repeated many times until the supernatant is neutral. The obtained solid is then dried in an oven at 120°C for 3h, and then calcined in a high-temperature furnace at 950°C for 3h to obtain a flaky wide bandgap filler with titanium dioxide coated on the surface.
[0042] The mass percentage of the granular wide bandgap filler in the thermal control coating provided by the present invention is preferably 17-33%, specifically 10%, 17% or 33%.
[0043] In the present invention, the particle size of the granular wide bandgap filler is preferably 6 to 500 nm, more preferably 10 to 20 nm, specifically 6, 10, 20, 500 or 1000 nm.
[0044] In the present invention, the types of the granular wide bandgap filler preferably include one or more of calcium carbonate, barium sulfate, aluminum oxide, silicon dioxide, magnesium oxide and boron nitride.
[0045] The mass percentage of the resin in the thermal control coating provided by the present invention is preferably 20%.
[0046] In the present invention, the resin preferably includes one or more of acrylic resin, epoxy resin, polyester resin, polyurethane resin and fluorocarbon resin.
[0047] The mass percentage of the dispersant in the thermal control coating provided by the present invention is preferably 1%, specifically 0.5%, 1% or 3%.
[0048] In the present invention, the dispersant preferably includes a dispersant for solvent-based coatings or a dispersant for water-based coatings, and the dispersant for solvent-based coatings preferably includes one or more of BYK163, BYK025, BYK161, BYK108, TEGODispers 676 and TEGO Dispers 655; the dispersant for water-based coatings preferably includes one or more of NXZ, SN5040, AC93, SN5027 and BYK190.
[0049] The mass percentage of the defoaming agent in the thermal control coating provided by the present invention is preferably 1%, specifically 0.5%, 1% or 3%.
[0050] In the present invention, the defoamer preferably includes an organosilicon defoamer, a polyether defoamer, a polyether-modified organosilicon defoamer or a mineral oil defoamer.
[0051] The mass percentage of the directional arrangement auxiliary agent in the thermal control coating provided by the present invention is preferably 2%.
[0052] In the present invention, the alignment aid preferably includes cellulose and / or modified polyamide wax.
[0053] In the present invention, the modified polyamide wax is preferably Arkema CRAYVALLAC SUPER.
[0054] The mass percentage of the solvent in the thermal control coating provided by the present invention can specifically be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.
[0055] When the thermal control coating is a solvent-based coating, the solvent preferably includes one or more of ethanol, ethyl acetate, butanone, propylene glycol methyl ether, a mixture of dibasic esters, butyl acetate, toluene, xylene, propylene glycol methyl ether acetate, dimethyl carbonate, NN dimethylformamide and propylene glycol; when the thermal control coating is a water-based coating, the solvent is preferably water.
[0056] The present invention also provides a method for preparing the thermal control coating described in the above technical solution, comprising the following steps:
[0057] The thermal control coating is obtained by mixing resin, dispersant, defoamer, directional arrangement assistant, lamellar wide bandgap filler, granular wide bandgap filler and solvent.
[0058] The present invention has no particular limitation on the specific manner of mixing, and any manner familiar to those skilled in the art may be used.
[0059] The present invention also provides the application of the thermal control coating described in the above technical solution in the field of construction.
[0060] The present invention has no particular limitation on the specific manner of the application, and any manner familiar to those skilled in the art may be used.
[0061] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0062] The performance test reference standard in the embodiments and comparative examples of the present invention is: JC / T 1040-2007; a wire rod is used to prepare the coating on the test tinplate, the coating thickness is controlled to be 80 μm (unless otherwise specified), and it is used for subsequent testing after drying at 70° C. for 24 hours.
[0063] The raw materials used in the examples and comparative examples of the present invention are:
[0064] The resin is acrylic resin;
[0065] Dispersant BYK163;
[0066] The defoamer is silicone defoamer D912R;
[0067] The aligning aid is cellulose CAB-381-0.5;
[0068] The solvent is propylene glycol methyl ether;
[0069] The surface of the sheet-like wide bandgap material is coated with titanium dioxide, and the preparation method is as follows:
[0070] Wet coating is adopted: a flaky wide bandgap filler suspension is prepared with a concentration of 5wt%, heated to 80°C, and then 2mol / L TiCl4 solution is added dropwise to the suspension, the pH value is adjusted to 6 with NaOH solution, the stirring speed is controlled at 500rpm, the solution after the reaction is allowed to stand for 2h and then centrifuged, the solid is washed with deionized water, the centrifugation and washing steps are repeated many times until the supernatant is neutral, and after drying in a 120°C oven for 3h, it is calcined at 950°C in a high-temperature furnace for 3h to obtain a flaky wide bandgap filler with surface coated with titanium dioxide.
[0071] Figure 2 This is a SEM image of flaky alumina coated with titanium dioxide. It can be seen that the alumina coated with titanium dioxide has a lamellar structure.
[0072] The preparation methods of the coatings of the embodiments of the present invention and the comparative examples are both: mixing various raw materials to obtain the coating.
[0073] Example
[0074] The composition and performance test of the thermal control coatings of Examples 1 to 9 are shown in Table 1. As can be seen from Table 1, Example 1 uses flaky aluminum oxide and granular aluminum oxide as fillers. When the coating thickness is 80 μm, the solar reflectivity is 91.3%, the coating is defect-free, and the mechanical and weather resistance properties are excellent; the difference between Example 2 and Example 1 is that a granular silica filler with a diameter of 500 nm is used. At 80 μm, the solar reflectivity of the coating is reduced to 90.2%; the difference between Example 3 and Example 1 is that the granular filler uses barium sulfate with a diameter of 1 μm, the pigment-to-base ratio of the coating is 3, and the mass ratio of flaky aluminum oxide to granular barium sulfate is 2:1; the difference between Example 4 and Example 1 is that the diameter of the flaky wide bandgap material is 5 μm; The difference between Example 5 and Example 1 is that the diameter of the flaky wide bandgap material is 5 μm, and the diameter / thickness ratio of the flaky wide bandgap material is 15, and the solar reflectivity of the obtained coating is 92.1%; the difference between Example 6 and Example 1 is that the diameter of the granular wide bandgap filler is 6 nm; the difference between Example 7 and Example 1 is that the fillers use flaky boron nitride and granular boron nitride, and the diameter, diameter / thickness ratio, and the added mass ratio of flaky and granular fillers are changed; the difference between Example 8 and Example 1 is that a combination of flaky boron nitride and granular aluminum oxide is used; the difference between Example 9 and Example 1 is that a combination of flaky boron nitride and granular barium sulfate is used.
[0075] Table 1 Composition and performance test results of thermal control coatings of Examples 1 to 9
[0076]
[0077] Comparative Example 1
[0078] Taking titanium dioxide as a comparative example, the solar reflectance curves of coatings of different thicknesses prepared from the thermal control coating of Example 1 and the coating of Comparative Example 1 were tested. The results are as follows: Figure 3 As shown, it can be seen that under the same pigment-to-base ratio, when the coating thickness is less than 35 μm, the solar reflectivity of Example 1 is lower than that of the coating with titanium dioxide as filler, and when the coating thickness is greater than 35 μm, the solar reflectivity of Example 1 is higher than that of the coating with titanium dioxide as filler. The highest solar reflectivity of the coating of Example 1 is greater than 94%, while the reflectivity of the coating with titanium dioxide as filler is difficult to exceed 90%.
[0079] Comparative Example 2
[0080] The same as Example 1, the only difference is that the alignment aid in Example 1 is replaced by a solvent of equal mass.
[0081] In Comparative Example 2, the lamellar wide bandgap fillers are arranged in a disordered manner during the drying process of the coating, which is called an unoriented arrangement; in Example 1, the lamellar wide bandgap fillers are arranged in an orderly manner in a certain direction during the drying process of the coating, which is called an oriented arrangement.
[0082] Figure 4 The reflectivity curves of the coatings of Comparative Example 2 and Example 1 are shown in Table 2. It can be seen that after adding the directional arrangement auxiliary agent to the coating, the flaky wide bandgap filler is oriented, and compared with the coating without adding the directional arrangement auxiliary agent, the sunlight reflectivity increases by 2.6%, the ultraviolet reflectivity increases by 7.92%, the visible light reflectivity increases by 3.17%, and the near-infrared reflectivity increases by 0.62%. It can be seen that the flaky filler after the flaky layers are oriented has a mirror reflection effect on the light, and the improved birefringence effect and mirror reflection improve the reflection efficiency of the light.
[0083] Table 2 Reflectivity data of coatings of Comparative Example 2 and Example 1
[0084]
[0085] Comparative Examples 3 to 11
[0086] The coating compositions and performance tests of Comparative Examples 3 to 11 are shown in Table 3. As can be seen from Table 3, the difference between Comparative Example 3 and Example 1 is that no directional arrangement additive is added to the coating, the arrangement of the flaky wide bandgap filler is disordered, and the reflectivity of ultraviolet, visible, and near-infrared is lower than that of Example 1, resulting in a lower sunlight reflectivity than that of Example 1; the difference between Comparative Examples 4 and 5 and Example 1 is the average diameter and average diameter to thickness ratio of the flaky aluminum oxide, wherein the diameter of the flaky material in Comparative Example 4 is too small, and the flaky arrangement cannot enhance the reflection effect, and the diameter / thickness of the flaky material in Comparative Example 5 is too small, resulting in the flaky being close to the granular filler, affecting the optical properties of the coating prepared by the coating; the difference between Comparative Example 6 and Example 1 is the diameter of the granular aluminum oxide, and the excessively large diameter leads to a decrease in the refraction and scattering effect of the particles on light, affecting the coating. The solar reflectivity of the layer is reduced; the difference between Comparative Example 7 and Example 1 is that the surface of the lamellar aluminum oxide is not coated with titanium dioxide, and there is no birefringence, which leads to a decrease in the solar reflectivity of the coating; the difference between Comparative Examples 8 and 9 and Example 1 is that only one of the fillers is added to the coating, and the pigment-to-base ratio of the coating remains unchanged, resulting in that a single filler cannot work synergistically to achieve good solar reflection; the difference between Comparative Example 10 and Example 1 is that the pigment-to-base ratio of the coating is 7, and an excessively large pigment-to-base ratio leads to hole defects in the coating, and the mechanical and weather resistance properties cannot meet the use requirements; the difference between Comparative Example 11 and Example 1 is that the pigment-to-base ratio of the coating is 1, the pigment-to-base ratio is too low, and the medium involved in refraction and reflection is too little, and the solar reflectivity of the coating is less than 80%.
[0087] Table 3 Coating composition and performance test results of Comparative Examples 3 to 11
[0088]
[0089] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A thermal control coating, characterized in that: The following components are included in mass percentage: Resin 15~30%, dispersant 0.5~3%, defoamer 0.5~3%, oriented alignment agent 0.5~3%, lamellar wide bandgap filler 10~40%, granular wide bandgap filler 10~40% and the rest solvent; The particle size of the granular wide bandgap filler is 6 to 500 nm; The flaky wide bandgap filler comprises a flaky wide bandgap material and a coating layer wrapping the flaky wide bandgap material, wherein the coating layer is made of TiO2, SiO2 or Al2O3; The sheet-like wide bandgap material has a thickness of 5-500 nm, a diameter of 3-50 μm, and a diameter / thickness ratio of 10-100; The types of the flaky wide bandgap material and the granular wide bandgap filler independently include one or more of calcium carbonate, barium sulfate, aluminum oxide, silicon dioxide, magnesium oxide and boron nitride.
2. The thermal control coating according to claim 1, characterized in that: The thickness of the coating layer is 100-300 nm.
3. The thermal control coating according to claim 1, characterized in that: The diameter of the sheet-shaped wide bandgap material is 5-10 μm.
4. The thermal control coating according to claim 1, characterized in that: The diameter / thickness of the sheet-like wide bandgap material is 15~30.
5. The thermal control coating according to claim 1, characterized in that: The particle size of the granular wide bandgap filler is 10-20 nm.
6. The thermal control coating according to claim 1, characterized in that: The resin includes one or more of acrylic resin, epoxy resin, polyester resin, polyurethane resin and fluorocarbon resin.
7. The thermal control coating according to claim 1, characterized in that: The alignment aid comprises cellulose and / or modified polyamide wax.
8. Application of the thermal control coating according to any one of claims 1 to 7 in the fields of construction, petrochemical industry, logistics and transportation, food storage, power communication and spacecraft.
Citation Information
Patent Citations
Heat insulation coating capable of reflecting solar heat rays
CN101121858A